Long term studies on compressive strength of high volume nano palm oil fuel ash mortar mixes - Hussin, Mohd. Warid (Penerbit UTM Press, 2015)
Palm oil fuel ash is a waste material that can be used as partial cement replacement. However, its reactivity as pozzolanic material depends on the size of the particle. This paper presents the effects of nano size palm oil fuel ash on the long term characteristics of mortar. The study covers basic properties of mortar including the morphology, porosity, compressive strength and microstructural with regards to the variations in the mix design of the mortar. The palm oil fuel ash used has gone through heat treatment and was ground to a nano size with the percentage replacement of cement used was 60%, 80% and 100%. The different types of mortar samples were cast in a 70x70x70mm cube for compressive strength test. All casting and testing of the samples were conducted in the laboratory at ambient temperature. The results show that the use of 80% nano size palm oil fuel ash has produced higher compressive strength at the age of 28 days by 32% compared to the control mortar. Grinding the palm oil fuel ash to a nano size particle has improved the reactivity of the ash and because of it is a waste material it reduces the cost of the mortar. The experimental result also show that the compressive strength of the 80% nano size palm oil fuel ash mortar at 365 days was 25% higher than its strength at 28 days. In addition, the porosity of the 80% nano palm oil fuel ash mortar was reduced by 51% at the age of 1 year. The overall results have revealed that the use of high volume nano palm oil fuel ash can enhances the mortar properties and due to the high percentage of replacement it can contribute to a more sustainable construction.